Religious Splinter Movement from Historical Perspective - Hermanu Joebagio (Millah: Journal of Religious Studies, 2008)
This article tries to analyze splinter groups of Islamic religion in Indonesia. Islamization in Indonesia has been building in the framework of universal values that containes democracy, i.e. hifdz-din, hifdz-nafs, hifdz-nasl, hifdz-mal, and hifdz-aql. Political change occurred in 1998 had triggered the emergence of splinters of Islamic religion; they were Salamullah, Isa Bugis, Baha’i, Madi in Palu, Qur’an Suci, and al-Qiyadah al-Islamiyah. They used atmosphere of pluralism and inclusivism to form their splinters’ community of religion. But, Ahmadiyah in historical perspective is different, because Ahmadiyah had existed before Indonesian Independence, and took part in resisting against Western colonization. The believe code of splinters of Islamic religion are deviant. They do not accepted Muhammad as the last prophet, change ‘shahadat’ and ‘shalat’. However, some people do not agree to punish or accuse them as being “sesat (deviant)”, because there still some chances to conversion.Keywords: Islam, doctrine, democracy, splinter group or movement, and violence.